Study of the effectiveness of shots on goal (with the foot) during the 2014 FIFA World Cup (case of the national teams of Germany, Argentina and Algeria) - D'bichi, Mounir; Hamici , Abdennour (sports creativity, 2025)
The main objective of this research is to analyze the effectiveness of goal shooting during the 2014 World Cup, and to determine the elements on what it depends. Methods: a sample of three teams (that participated in the 2014 World Cup), was analyzed (Germany, Argentina and Algeria) using observation as a means of analysis. Results: We found that goal shooting’s success changes according to the foot contact surface, the shooting area and the type of shots, we also concluded that the goal shooting’s control leads the teams to achieve remarkable results in this type of competition. Conclusion: Through the matches’ analysis, we found that the goal shooting’s effectiveness depends on the foot contact surface, as well as on the shots’ area and type. Key words: goal shooting, effectiveness, Football world Cup 2014, foot contact surface, shooting area, shooting type